Dried blood spots can help decrease the burden on patients dually infected with multidrug-resistant tuberculosis and HIV. Issue 3 (10th June 2016) - Zuur, Marlanka A.; Akkerman, Onno W.; Touw, Daan J.; van der Werf, Tjip S.; Cobelens, Frank; Burger, David M.; Grobusch, Martin P.; Alffenaar, Jan-Willem C.
HIV and tuberculosis (TB) are among the leading causes of death due to an infectious disease worldwide [1]. HIV co-infection was present in 12% of all TB cases in 2014; the African region accounted for 74% of those [1]. It has become crystal clear that both infections must be addressed simultaneously. Additionally, multidrug resistance (MDR) and extensive drug resistance (XDR) aggravate the problem even more [2]. The risk of having a poor MDR-TB treatment outcome is up to 10-fold higher among HIV co-infected individuals [3]. The pill burden for patients with MDR-TB with HIV co-infection is high and consists of a combination of at least six to 10 different drugs [2]. Therefore, drug–drug interactions, adverse drug reactions and/or suboptimal plasma concentrations are common [3]. Ultimately, the goal is to tailor both TB and HIV treatment (precision treatment) to optimise outcome and reduce adverse drug events in a way that is cost-effective and feasible worldwide. Of note, in nonaffluent settings where there is high disease co-endemicity, this requires a minimalist yet effective approach while resources are limited. What are needed are tools to determine the concentrations of all drugs, and treatment response markers by means of HIV viral load, and sputum smear and culture. TDM with dried blood spots can simply and simultaneously monitor treatment in patients with MDR-TB with HIV http://ow.ly/TKIo300mwIY